Impact of Service Quality on Customer Satisfaction and Loyalty in Indonesia’s Water Providers: Literature Review - Fadillah, Azka Azizi; Vindiana, Afina Putri; Octasylva, Annuridya Rosyidta Pratiwi; Tampubolon, Edward Sahat (Institut Teknologi Indonesia, 2025)
This literature review explores the influence of service quality on customer satisfaction and loyalty in clean water service providers, with a specific focus on the challenges faced by such providers in Indonesia. Service quality, which includes dimensions such as tangibles, reliability, responsiveness, assurance, and empathy, plays a crucial role in determining customer satisfaction and loyalty. The study analyzes previous research to highlight the impact of these dimensions on customer perceptions and loyalty. It also identifies challenges faced by clean water service providers, including issues such as uneven water distribution, pipe leaks, inaccuracies in water meter readings, and delays in responding to customer complaints. The review emphasizes the importance of improving service quality through employee training, enhancing transparency, and utilizing technology to better serve customers. The findings of this review provide recommendations for clean water service providers to improve service quality, ultimately increasing customer satisfaction and loyalty.